Modeling and analysis of electrode wear and white layer thickness in die-sinking EDM process through response surface methodology - Caydas, Ulas; Hascalik, Ahmet (Springer London Ltd, 2008)
In this study, an attempt has been made to model electrode wear (EW) and recast layer thickness (WLT) through response surface methodology (RSM) in a die-sinking EDM process. A central composite rotatable design (CCRD) involving three variables with five levels has been employed to establish a mathematical model between input parameters and responses. Pulse on-time, pulse off-time and pulse current were changed during the tests based on the CCRD. The results of analysis of variance (ANOVA) indicated that the proposed mathematical models obtained can adequately describe the performances within the limits of factors being studied. The experimental and predicted values were in a good agreement.
Keywords: EDM; electrode wear; response surface methodology; white layer thickness